EFFECT OF NANO SILICA, NANO ALUMINUM, AND NANO TITANIUM ADDITIONS ON FLEXURAL AND SHEAR BEHAVIOR OF RC BEAMS - Gabr, Ahmed Shaban Abdel-Hay (International Journal of Advanced Science and Technology, 2020)
In the present study; the effect of nano-SiO2, nano-Al2O3 , and nano-TiO2 additions on the flexural and shear behavior of reinforced concrete beams is investigated. The experimental program contains testing of 12 RC beams divided into three groups; the first and second group consists of four beams tested until failure in bending with bottom reinforcement ratio of 0.837% and 1.88 % respectively, while the third one consists of four beams tested until shear failure was reached. Each group consists of one control beam, one beam with 3% of nano-SiO2, one beam with 1% of nano-Al2O3, and one beam with 1% of nano-TiO2. Based on the analysis of experimental data, it was concluded that the addition of nanoparticles, mainly nano-Al2O3, to the concrete mixtures can lead to a flexural strength increase but using 1% nano- TiO2 addition is more effective to enhancement the beam shear strength.